Spiritual well-being as a protective factor for endothelial dysfunction in clinically healthy adults - Andre Casarsa; Pedro Bastos de Medeiros; Julio Cesar Tolentino; Isadora de Sa Guimaraes; Kelen Carolina Silva Cruz; Leticia Silva Flor dos Santos; Matheus Nakazato Tinoco; Maria de Fatima Martins Gil Dias; Ana Lucia Taboada Gjorup; Sergio Luis Schmidt (PLoS ONE, 2025)
Background Endothelial dysfunction (ED) is an early marker of cardiovascular disease (CVD), influenced by both physiological and psychosocial factors. While depression and anxiety are known contributors to ED, the role of spiritual well-being (SWB) in vascular health has been relatively less explored in the literature. Objective To investigate the association between SWB and ED in clinically healthy adults, controlling for mental health variables and conventional cardiovascular risk factors. Methods In this cross-sectional study, 148 individuals aged 18–60 years were assessed using validated instruments: FACIT-Sp for SWB, PHQ-9 for depression, GAD-7 for anxiety, and brachial artery flow-mediated dilation (FMD) for endothelial function. Logistic regression and discriminant analyses were performed to identify independent predictors of ED and the spiritual dimensions most associated with vascular health. Results ED was identified in 39.2% of participants. Multivariate logistic regression indicated that SWB (OR = 0.929; p = 0.005), body mass index (OR = 1.130; p = 0.016), generalized anxiety disorder (OR = 2.551; p = 0.035), and major depressive episode (OR = 3.740; p = 0.038), were significantly associated with ED. Among these, SWB was significantly inversely associated with ED even after excluding participants with anxiety or depression. Discriminant analysis further indicated that inner peace and life purpose—but not faith—significantly distinguished individuals with and without ED. Conclusion SWB, particularly dimensions related to inner peace and meaning, is independently associated with preserved endothelial function in healthy adults. These findings support the inclusion of psychosocial and spiritual dimensions in cardiovascular risk assessment and prevention strategies.